(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Forward roll is one of the fundamental skills in floor gymnastics that students must master in Physical Education, Sports, and Health (PJOK) learning. However, many students experience difficulties in performing the movement correctly due to limited motor coordination, lack of confidence, and insufficient individualized feedback during the learning process. This study aimed to improve the forward roll skills of Grade 10 students in Class X-1 at State Senior High School 2 Martapura through the implementation of video feedback media in floor gymnastics learning. The study employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 35 students of Class X-1 in the even semester of the 2025/2026 academic year. Data were collected through performance tests, observations, and documentation, and analyzed using descriptive and comparative techniques. The findings revealed a substantial improvement in students’ forward roll performance after the implementation of video feedback. Classical learning mastery increased from 37.14% in the pre-cycle (13 out of 35 students achieving mastery) to 60.00% in Cycle I, and further improved to 88.57% in Cycle II. Similarly, the average class score increased from 64.18 (Poor category) in the pre-cycle to 73.19 (Fair category) in Cycle I, and reached 79.56 (Good category) in Cycle II. The integration of peer-feedback activities in small groups during Cycle II further enhanced students’ learning outcomes and engagement. In conclusion, video feedback is an effective and innovative instructional strategy for improving forward roll skills and can be recommended for PJOK learning at the secondary school level.